TAKING BENEFITS FROM USING TRACK CHANGES AS A GRAMMAR CONSCIOUSNESS-RAISER (RETAIN, 2014)
TAKING BENEFITS FROM USING TRACK CHANGES AS A GRAMMAR CONSCIOUSNESS-RAISER Reiza Ayu Puspitasari English Education, Faculty of Languages and Arts, State University of Surabaya Email: ayu_reiza@yahoo.com Ahmad Munir English Education, Faculty of Languages and Arts, State University of Surabaya Abstrak Track Changes telah digunakan dalam pengajaran mata kuliah Advanced English Grammar untuk mahasiswa semester tiga di Kelas A angkatan 2012 Jurusan Pendidikan Bahasa Inggris, Universitas Negeri Surabaya. Oleh karena itu, penelitian ini ditujukan untuk mendaftar kesalahan-kesalahan grammar yang disadari mahasiswa pada saat Track Changes digunakan, menjelaskan bagaimana Track Changes meningkatkan kesadaran grammar mahasiswa dan menjelaskan bagaimana mahasiswa menjadi sadar akan kesalahan-kesalahan grammar pada saat Track Changes digunakan. Penelitian studi kasus ini menggunakan analisis dokumen, wawancara dan kuesioner sebagai metode pengumpulan data. Tiga puluh mahasiswa dipilih sebagai subjek penelitian. Meskipun demikian, analisis esai hanya berfokus pada lima esai mahasiswa. Pertimbangan ini didasarkan pada kemauan mahasiswa untuk berpartisipasi dalam wawancara. Hasil menunjukkan bahwa: Pertama, kesalahan-kesalahan grammar yang disadari mahasiswa pada saat Track Changes digunakan tidaklah terbatas, seperti kata kerja akusatif, kata ganti, kata kerja, bentuk jamak, kata benda, klausa adjektiva, gerund dan kata sifat. Kedua, Track Changes telah berhasil meningkatkan kesadaran grammar mahasiswa karena jumlah dan jenis-jenis kesalahan-kesalahan grammar yang ditemukan di esai mahasiswa menurun. Ketiga, mahasiswa menjadi sadar akan kesalahan-kesalahan grammar pada saat Track Changes digunakan dengan melakukan revisi dan mendapat revisi. Kata Kunci: Advanced English Grammar, consciousness-raising, Track Changes Abstract Track Changes has been incorporated in the teaching of Advanced English Grammar unit for the third semester students of Class A 2012 batch of English Education study program in State University of Surabaya. Thus, this study aimed at listing the grammatical errors the students have become conscious when Track Changes used, explaining how Track Changes have raised students’ grammar consciousness and explaining how the students become conscious of grammatical errors when Track Changes used. Document analysis, interview and questionnaire were employed in this case study research. Thirty students were chosen as the participants. However, the analysis of the essay only focused on five essays. The consideration was based on the students’ willingness to participate in the interview. The results showed that: First, the grammatical errors the students have become conscious when Track Changes used were not limited such as accusative verbs, pronoun, verbs, plural forms, noun, adjective clause, gerund, and adjective forms. Second, Track Changes have successfully raised students’ grammar consciousness because the total and variety of grammatical errors found in students’ essays decreased. Third, the students become conscious of grammatical errors when Track Changes used by doing revision and getting revision. Keywords: Advanced English Grammar, consciousness-raising, Track Changes INTRODUCTION In the academic year of 2012/2013, grammar in English Language program of State University of Surabaya was taught through two units; Intermediate English Grammar that should be completed in the second semester and Advanced English Grammar that was taken in the third semester. Before taking these two units, the students had already been taught grammar that was integrated in Intensive Course (IC) unit (Buku Pedoman Universitas Negeri Surabaya 2012/2013, 2012). It was found that in one of the four classes of Advanced English Grammar unit that was Class A, the students of 2012 batch learnt grammar by doing peer editing on writing products using Track Changes technology besides doing exercises on Test of English Proficiency (TEP) samples. Assigning the students to do peer editing in learning Advanced English Grammar is aimed at facilitating the detection and correction of grammatical errors. This activity is associated with an approach to teaching grammar called consciousness-raising. Ellis (2003) points out that consciousness-raising emphasizes the forms more than the meanings, and is directed to make the students aware of how some linguistic features work. Nevertheless, though the students focus on the form of the grammar structure, it does not mean that focus on meaning is totally abandoned. This is because the students are also engaged in meaning-focused use of the target language as they solve the grammar problem (Fotos, 1994). Additionally, studies on the process of teaching grammar show that the creation of systems specifically designed to address students’ need such as clear feedback, and teacher’s needs such as elimination of repetitive tasks, increased learner independence, and identification of error patterns, becomes affordable in this current time due to the availability of advanced technology coupled with recent research dealing with learner texts (Hegelheimer & Fisher, 2006). The available advanced technologies (Kuo et al., 2002, Cowan, Choi, & Kim, 2003, Hegelheimer & Fisher, 2006) provide the facilities such as to detect users’ persistent errors and give adequate help, investigate if persistent errors can be eradicated, and raise learner awareness of troublesome grammatical features. The findings prove that technologies in this recent time have been integrated into teaching English, particularly in teaching grammar. In Indonesia, the use of technology has been implemented, particularly in teaching writing, in which grammar becomes an inseparable part of it. Munir and Nugroho (2008) conducted a study on the use of Track Changes to find out if the students could notice the language errors on their essays, whether they did not make the same errors on their essay revisions, what action they took on the parts of essays revised by the lecturer using Track Changes, whether or not there was different quality on the language use on draft 1, 2, and so forth after given feedbacks by the lecturer using Track Changes. The conclusions were the implementation of Track Changes was interesting in a way of directing the students’ attention on the parts of essays that needed to get revisions. However, this study indicates that the improvement the students made on their essays, particularly on the language use, did not come from the students’ own ability but the lecturer’s correction and comments on the Track Changes. The findings from the previous research about the use of Track Changes play a key role in designing this research. While the previous research focused on the lecturer and students’ interactivity with the technology used in writing unit, this research was conducted to investigate in a greater depth about the students, peers, and the lecturer’s interactivity and to find out how Track Changes was used to raise students’ consciousness on grammatical errors in a university grammar class. Thus, this study investigated the process of teaching grammar on Advanced English Grammar unit taken by the third semester students of Class A 2012 batch in English Education program of State University of Surabaya and the benefits of making use of Track Changes. RESEARCH METHODS This study was a qualitative study aimed at describing social phenomenon of taking benefits from using Track Changes as a consciousness raiser in a university grammar class as they occurred naturally since this took place in the natural setting, without any attempts to manipulate the situation under study (Dornyei, 2007). This was also a case study research since the observation was only done in one of the four grammar classes in English Education Program of State University of Surabaya, as indicated by Ary, et al. (2010). Document analysis, interview and questionnaire were employed in this study to list the grammatical errors detected by peer editors, to explain how students’ grammar awareness improved, and to find out the internal experience of the students regarding the use of Track Changes in peer editing activities. In this study, 30 students from class A Advanced English Grammar 2012 batch of the third semester majoring in English Education program became the participants. They were chosen under the consideration that whilst taking Advanced English Grammar unit, the students were introduced to the use of Track Changes in doing peer editing on writing products while learning grammar. However, the analysis of the essay only focused on five essay drafts. The consideration was based on the students’ willingness to participate in the interview. The first, second, and third version of five female students’ essay drafts were collected by copying the files from the lecturer. The essays collected were read, scrutinized, and searched for the Track Changes which spotted the grammatical errors found by peer editors. Then, the grammatical errors the peer editors detected and marked through Track Changes were classified in three categories. Those were: could spot the errors and could successfully correct them, could spot the errors but could not successfully correct them, and could not spot the errors and could not correct them. The examples of each category were given. Also, interview was constructed in the form of semi-structured interview asking for the students’ opinion on the use of Track Changes, what they have learnt from giving comments and suggestions towards their friends’ essays, and the benefits of Track Changes for spotting grammatical errors. Additional questions were asked depend on the students’ response to each question given. Besides, the questionnaire was constructed in the form of Likert scales in favorable or positively stated items. Strongly agree is scored 5, agree is scored 4, undecided or do not know is scored 3, disagree is scored 2, and strongly disagree is scored 1. The students were directed to select the response category that best represents their reaction to each statement (Ary, et al., 2010). The questionnaire contained 11 statements of the mechanism, the ease and the benefits of using Track Changes. In addition, the 11 Likert-scale items were tested for reliability coefficients using Cronbach’s alpha. According to Sax (1989), a reliability coefficient of more than 0.6 is required for a self-designed text or survey. The all variables scale in this study achieved alpha of 0.69 that was satisfactory. Furthermore, to explain how Track Changes have raised students’ grammar consciousness, the quality of the first essay drafts written by the students were compared to the third essay drafts submitted to the lecturer after being edited by peer editors and the essay’s owners. The quality was judged based on the total and variety of the grammatical errors the students made on the first and third version. Besides, to investigate how the students become conscious of grammatical errors when Track Changes used, interview transcript was searched for the words and phrases which represented the students’ view on the use of Track Changes. These were then interpreted for their meanings. Moreover, to find out the view of the students who were given Track Changes and those who gave Track Changes, responses to the 11 items in the questionnaires were coded and imported into SPSS for descriptive statistics analysis to show the trends of their opinions of the mechanism, the ease, and the benefits of using Track Changes. RESULTS AND DISCUSSION To reveal the benefits of using Track Changes as a grammar consciousness raiser, the results show the grammatical errors detected by peer editors, explain how students’ grammar awareness improved, and elaborate the internal experience of the students regarding the use of Track Changes in Advanced English Grammar unit. The grammatical errors the students have become conscious when Track Changes was used in grammar lesson The first example found showed that student 1 made a sentence “Some of them let the acnes gone by itself” that contain two grammatical errors. First, the word let belongs to accusative verbs that should be followed by infinitives. Therefore, the peer editor revised it to be “Some of them let the acnes go”. Besides, the peer editor edited the pronoun itself to be themselves to represent the plural object acnes. These revisions prove that the peer editor could spot the grammatical errors in student 1’s essay and could successfully correct them. This was also done by the other four peer editors who edited student 2, student 3, student 4, and student 5’ essay. Nevertheless, it was also found that in spotting the grammatical error in student 1’s essay such as “Because exercise can really help relieve stress and acnes”, the peer editor revised it to be “Because exercise can really help relieve stress which causing acnes” which is inappropriate. The object pronoun which of the adjective clause should be followed by third person singular causes because the object stress is in a singular form. Only if which is omitted, the use of the progressive verb causing is acceptable. This phenomenon shows that the peer editor could spot the grammatical error in student 1’s essay but could not successfully correct it. The same phenomena were also found on student 2 and student 4’s essay. The cases for peer editors who could spot the errors and could successfully correct them or could spot the errors but could not successfully correct them using Track Changes prove the finding from Hegelheimer and Fisher (2006) that the availability of the technology increases learner independence and identification of error patterns. This is contradictory with Munir and Nugroho (2008) who indicated that the improvement the students made on their essays when Track Changes was used, particularly on the language use, did not come from the students’ own ability but the lecturer’s corrections and comments in Track Changes. However, the third example shows that the grammatical error found in student 1’ essay could not be spotted by the peer editor. An utterance such as “Take some exercise also a good way to cure acnes” should be revised to be “Taking some exercise is also a good way to cure acnes”. The verb take should be changed into gerund form taking because it becomes the subject of the sentence. In addition, there is also an omission of verb is that was not spotted and thus the peer editor could not correct the errors. The same condition also happens on student 2, student 3, and student 5’s essay. The above explanation shows that the grammatical errors the students have become conscious when Track Changes used were not limited such as accusative verbs, pronoun, verbs, plural forms, noun, adjective clause, gerund, and adjective forms. Thus, it is proven that the favorable results of the pilot study which used only one task dealing with one specific grammatical feature are consistent when the students given a number of tasks dealing with different grammatical structures as found by Fotos (1994). How Track Changes have raised students’ grammar consciousness After getting revision on the second essays, the grammatical errors in student 1’s essay decreased from the total of 17 to be 9 errors in the third essay. Errors in grammatical aspects such as verb tense, accusative verb, object pronoun, parallelism, diction, noun omission, and article in student 1’s first essay were not found in her third essay. This condition also happened on student 2, student 4, and student 5 that showed significant decrease on the total and variety of grammatical errors in their first essays compared to the third version of the essays written. However, the condition happened in student 3 shows that the same grammatical error was found in the first and third essay. This was as a result of the inability of the peer editor in spotting the error on the second essay which was “It is an intelligence snake” (Student 3’s essay) which caused the essay owner did the same error in her third essay. The significant decrease on the total and variety of grammatical errors in students’ first essays compared to the third version of the essays written shows that Track Changes have successfully raised students’ grammar consciousness. Thus, the decision to choose Track Changes may be made on the consideration that the technology has the ability to facilitate acquisition or improvement on grammatical competence as stated by Stockwell (2007) that choosing technology can be based on pedagogical objectives that means particular technology is selected due to specific features it has. Besides, it confirms Granger et al. (2007) who found that the combination of technology is beneficial for raising language awareness. How the students become conscious of grammatical errors when Track Changes was used in Advanced English Grammar unit The results of the descriptive statistics on the students’ view related with the mechanism, the ease, and the benefits of using Track Changes shows that items 1, 2, and 3 have mean scores higher than 4 which mean the students’ stance exists in between scale 4 representing agree and 5 representing strongly agree. This means the students confirm that they understand the mechanism of operating Track Changes. Regarding the ease, the students give quite different responses toward item 4 and item 5. The mean score for item 4 is higher than 4, indicating the students agree that giving comments or suggestions toward their friend’s essay is easier when using Track Changes. This is supported by the student’s opinion given in the interview such as “Because I think it’s easy to use and it’s not much time consuming different with editing on papers” (Student 1). Additionally, Student 5 expresses her preference to use Track Changes in a response such as “It makes me easier to correct my friend’s essay. I prefer using Track Changes for editing my friend’s essay by typing rather than writing the comments”. This is in line with Ho and Savignon (2007) who found that many learners indicated that they preferred typing instead of writing while providing feedback. Furthermore, the mean score of 3.97 which item 5 has, indicates that the students tend to agree that understanding the feedbacks given by peer editor is easier when Track Changes used. It was shown in a response such as “usually, there is a line next to a sentence that is given Track Changes. And we know that the word is wrong, so we can find out what’s wrong with that. And then, we know that there is wrong grammatical construction” (Student 5). However, understanding the feedbacks from peer editor is sometimes confusing, as well. This can be proven from Student 3 saying “I think that’s correct but they said that it’s false, it’s not like that. Sometimes, we make negotiation, and share arguments”. This is contrary to Ho and Savignon (2007) who found that lack of oral discussion during peer review sessions when Track Changes used was found to be an obstacle. Also, when the students felt confuse to accept or reject the revision made by peer editors, the lecturer gave comments that the students perceive as beneficial such as in “Sometimes, my friend corrects sentence that I think is right. If I found something like that, I usually go to the lecturer to consult about that” (Student 1) and “My lecturer usually give feedback and I think it is better comparing to directly accepting my friend’s feedbacks on my essay because I think they are not expert in grammar. Sometimes, it’s hard to know whether my friend’s correction is right or not, so my lecturer’s feedback makes it clear for me” (Student 3). This is as suggested by Fotos and Ellis (1991) who believe that the proficiency gains would have been higher with a more detailed explanation of the requirements of the task, previous experience in pair or group work, and teacher’s feedback on the solution of the task. Besides the mechanism and the ease, the students were also asked about their view on the benefits of Track Changes. It is found that there are two different trends of the mean scores; lower than 4 and higher than 4. Item number 6 has a mean score of 3.97 which mostly reaches 4 indicating that most students tend to agree that using Track Changes to show their friends’ errors makes them aware of grammatical features. This is supported from the responses given during the interview such as “as a peer editor, Track Changes help me to show the grammatical errors in my friend’s essay easily. So, she can know that there is something wrong” (Student 5) and “we (become) more sensitive about error in my friend’s essay” (Student 1). Moreover, the students agree that the errors shown in Track Changes help them aware of grammatical features as stated by Student 2 “(from) the second step, we know that our grammar is not perfect, we still found many grammatical errors but I ask to my friend and lecturer and sometimes I open Betty Azar book and my grammar gets better”. This upholds the findings from Yip (1994) who found that a C-R session class can be effective for directing students’ attention to the ungrammatical constructions, and Munir and Nugroho (2008) who believe that the implementation of Track Changes is interesting in a way of directing students’ attention on the parts of essays that need to get revision. By using Track Changes, the language errors on students’ essays could be directly showed to them. In addition, the students tend to agree (M=3.97, SD= .823) that when Track Changes used, they could detect their friends’ errors and could easily correct them. However, item number 9 has a mean score of 3.14 that means the students’ stance exists in between scale 3 representing undecided or do not know and 4 representing agree. In another word, the students tend to have no idea whether they could detect their friend’s errors but hardly correct them or not when Track Changes used. This means, the students were not so sure if correcting errors in their friend’s essay was hardly done. Moreover, item number 10 shows the students agree that the use of Track Changes helps essay editing activities more efficient. Besides, the mean score of 3.93 which item number 11 has, indicates that the students tend to agree that Track Changes makes grammar learning more engaging as stated by Student 3 “I want to say that grammar is one of my favorite lectures. So, everything new about grammar, I am very interested about it. One of this is Track Changes. So I think Track Changes is something that motivates me in learning grammar”. Furthermore, students’ responses on the semi-structured interview also reveal essential information about the benefits of Track Changes that leads to the explanation of how the students become conscious of grammatical features when Track Changes used in Advanced English Grammar unit. Those were expressed in comments such as “I become more… very aware about the grammar form, function, and meaning. So, for all this time I just consider the form and the meaning, not the function. I become more aware about the function” (Student 1) and in “I learn so much from Track Changes, such as grammar that my friends know but I don’t know, and then the comments from lecturer also help me. Before this, I don’t know, after I use Track Changes and my lecturer gives comments, I become understand fragment, the use of active and passive voice that sometimes confusing” (Student 4). These are in line with Ellis (2003) who stated that C-R is directed to make the students aware of how some linguistic features work and Scott and Fuente (2008) who concluded that the outcome of C-R tasks is awareness and discovery of how a specific structure works. However, opinions such as “sometimes, when my lecturer give us that kind of exercise using Track Changes, it’s quite boring” (Student 3) and “But sometimes I feel bored because Track Changes was used in most of our grammar class” (Student 4) indicate the students found that using Track Changes is sometimes boring. Additionally, Student 4 saying “There are many rules and steps taken for editing the essay. That’s make me bored” explained why the student feels bored sometimes when using Track Changes for peer editing activities. Despite expressing the boredom, the student still emphasizes the use of Track Changes as helpful, as stated by Student 3 “But I think it’s still very useful for us”. CONCLUSIONS The results and discussions presented previously become the sources of drawing the conclusions of this study. First, the grammatical errors the students have become conscious when Track Changes used in grammar lesson were not limited to particular grammatical structure since in peer editing activities the students did not focus on one C-R task dealing with one specific grammatical feature. There were three categories of peer editors’ responses in Track Changes concerning the grammatical errors spotted, those were could spot the errors and could successfully correct them; could spot the errors but could not successfully correct them; and could not spot the errors and could not correct them. This indicates that Track Changes increases students’ independence because the corrections and comments in Track Changes came from the students (peer editors), not the lecturer. Second, Track Changes has successfully raised students’ grammar consciousness. After getting the revision on the second essays from peer editors using Track Changes, the total and variety of grammatical errors in students’ final essays decreased compared to the first essays. Thus, the reason of making use of Track Changes might be pedagogical objective that is facilitating improvement on grammatical competence. Third, the students become conscious of grammatical errors when Track Changes was used in Advanced English Grammar unit as results of doing revision and getting revision. After doing revision, peer editors made negotiation with their friends about the grammatical errors spotted in Track Changes. When there was confusion to accept or reject the revision, they read grammar book and they were also given feedbacks from the lecturer. This makes the students aware of grammatical features that they did not know before. In addition, the students become conscious of grammatical errors because Track Changes directs their attention on parts of the essays that contained errors. REFERENCES Ary, D., Jacobs, L. C., & Sorensen, C. K. (2010). Introduction to Research in Education (8th Edition ed.). Belmont: Wadsworth Cengage Learning. Buku Pedoman Universitas Negeri Surabaya 2012/2013. (2012). Surabaya: Fakultas Bahasa dan Seni. Cowan, R., Choi, H. E., & Kim, D. H. (2003). Four questions for error diagnosis and correction in CALL. CALICO Journal, 20(3), 451-463. Dornyei, Z. (2007). Research Methods in Applied Linguistics: Quantitative, Qualitative, and Mixed Methodologies. Oxford: Oxford University Press. Ellis, R. (2003). Tasks-Based Language Learning and Teaching. Oxford: Oxford University Press. Fotos, S., & Ellis, R. (1991). Communicating about grammar: A task-based approach. TESOL Quarterly, 25(4), 605-628. Fotos, S. S. (1994). Integrating Grammar Instruction and Communicative Language Use Through Grammar Consciousness-Raising Tasks. TESOL Quarterly, 28(2), 323-351. Granger, S., Kraif, O., Ponton, C., Antoniadis, G., & Zampa, V. (2007). Integrating learner corpora and natural language processing: A crucial step towards reconciling technological sophistication and pedagogical effectiveness. ReCALL, 19(3), 252-268. Hegelheimer, V., & Fisher, D. (2006). Grammar, Writing, and Technology: A Sample Technology-supported Approach to Teaching Grammar and Improving Writing for ESL Learners. CALICO Journal, 23 (2), 1-24. Ho, M.-C., & Savignon, S. J. (2007). Face-to-face and Computer-mediated Peer Review in EFL Writing. CALICO Journal, 24(2), 269-290. Kuo, C.-H., Wible, D., Chen, M.-C., Sung, L.-C., Tsao, N.-L., & Chio, C.-L. (2002). The design of an intelligent web-based interactive language learning system. Journal of Educational Computing Research, 27(3), 229-248. Munir, A., & Nugroho, H. m. A. (2008). A Model of Essays Consultation in the Writing Process of Writing III Using Track Changes. State University of Surabaya. Sax, G. (1989). Principles of educational and psychological measurement and evaluation (3rd ed.). Belmont, CA: Wadsworth Publishing. Scott, V. M., & Fuente, M. J. d. l. (2008). What's the problem? L2 Learners' Use of the L1 During Consciousness-Raising, Form-Focused Tasks. The Modern Language Journal, 92, 100-113. Stockwell, G. (2007). A review of technology choice for teaching language skills and areas in the CALL literature. ReCALL, 19(2), 105-120. Yip, V. (1994). Grammatical consciousness-raising and learnability. In T. Odlin (Ed.), Perspective on pedagogical grammar (pp. 123-139). Cambridge: Cambridge University Press.